Visualization and quantification of injury to the ciliated epithelium using quantitative flow imaging and speckle variance optical coherence tomography. Issue 1 (December 2017) - Gamm, Ute; Huang, Brendan; Mis, Emily; Khokha, Mustafa; Choma, Michael
Abstract Mucociliary flow is an important defense mechanism in the lung to remove inhaled pathogens and pollutants. Disruption of ciliary flow can lead to respiratory infections. Multiple factors, from drugs to disease can cause an alteration in ciliary flow. However, less attention has been given to injury of the ciliated epithelium. In this study, we show how optical coherence tomography (OCT) can be used to investigate injury to the ciliated epithelium in a multi-contrast setting. We used particle tracking velocimetry (PTV-OCT) to investigate the cilia-driven flow field and 3D speckle variance imaging to investigate size and extent of injury caused to the skin ofXenopus embryos. Two types of injuries are investigated, focal injury caused by mechanical damage and diffuse injury by a calcium chloride shock. We additionally investigate injury and regeneration of cilia to calcium chloride onex vivo mouse trachea. This work describes how OCT can be used as a tool to investigate injury and regeneration in ciliated epithelium.